SYNTHESIS AND BIOPROTECTIVE PROPERTIES OF HYBRID MONTMORILLONITE-POLYSACCHARIDE COMPOSITES - E.T. Talgatov,; A.S. Auyezkhanova,; A.K. Zharmagambetova,; U.N. Kapysheva,; Sh.K. Bakhtiyarova,; B.I. Zhaksymov, (Academic Scientific Journal of Chemistry, 2019)
Polysaccharide-silicate composites based on pectin (PC) and Tagansorbent (TS) - montmorillonite of the Tagansky deposit – have been synthesized. The calculated amount of pectin in the composites was 5, 10, 20, and 40%. Viscosimetric method showed the degree of fixation of pectin on the surface of the inorganic sorbent Samples of the prepared pectin-containing composites have been studied by various physicochemical methods (IRspectroscopy, scanning electron microscopy, X-ray diffraction). The data of IR – spectroscopy and scanning electron microscopy showed the presence of polysaccharide in the prepared composites. The IRS method has confirmed the shifting absorption bands of the pectin functional groups in the polymer fixed to Tagansorbent. SEM images has demonstrated modification of the surface of inorganic sorbent after treatment with pectin. The adsorption of lead ions (Pb2+) on the developed polysaccharide-silicate composites has been studied for further their testing as enterosorbents. The optimum adsorption activity was observed in the presence of the composite with a pectin content of 9.4%. The polysaccharide-silicate composites have shown bioprotective properties at the study of the total proteolytic activity (TPA) of the intestinal walls of lead-intoxicated rats.